La estructura simbólico-imaginaria del "Quijote" : sistema expresivo y valor poético - Salazar Quintana, Luis Carlos (Biblioteca filológica hispana ;, 2015)
This study intends to demonstrate the organic unity of imaginary time in Cervantes' Quixote as the source of its poetic significance, and to show that the fundamental design of the novel is based on a structure of convergences and synthesis that express the narrative's temporality in imaginary forms.